Transplacental digoxin treatment in prenatal cardiac problems in singleton pregnancies - meta analysis (based on literature: 1992-2015) - Strzelecka, Iwona; Respondek-Liberska, Maria; Słodki, Maciej; Zych-Krekora, Katarzyna; Cuneo, Bettina (Prenatal Cardiology, 2016)
Based on fourteen case reports from various centres from 1992–2015 and three original studies in 2006–2011, 122 fetuses were subjected to analysis. In these reports, transplacental digoxin treatment was administered to different cardiac anomalies such as SVT, Ebstein’s anomaly, critical AS , absent pulmonary valve syndrome, complete heart block, in foetuses with aneurysm/diverticulum of LV, in tricuspid atresia or dysplasia, rhabdomyoma, pulmonary atresia, HLHS with fibroelastosis, in TTTS and in extracardiac anomalies such as atriovenous malformation or sacrococcygeal teratoma. There was no statistical difference to suggest (Chi-square test) that digoxin was more efficient to control fetal arrhythmias than fetal congestive heart failure in nonarrhythmic patients. Conclusions: Foetal cardiac insufficiency may appear due to different reasons (in normal heart anatomy or in heart defects, in normal sinus rhythm or due to foetal arrhythmias: tachycardias or severe bradycardia) and may be a cause of intrauterine demise. So far, we do not have strong evidence that digoxin treatment may prevent foetal death or prematurity. More research is needed to ascertain if the prolonging of pregnancy resulted from digoxin treatment or if improvement in foetal circulatory insufficiency was influenced by spontaneous regression of foetal cardiac symptoms.